Profile of Drug-Resistant Tuberculosis Patients at the Haji Regional Hospital, East Java Province in 2019-2022 - Meddy Setiawan; Raditya Widya Surianata; Yolla Gitamaya Yustikasari; Nurani Hakiki; Annisa Brilian Ornadi; Ridho A'bid Permana (Universitas Muhammadiyah Malang, 2024)
Objective: To determine the profile of TB cases that are resistant to antibiotics and the resistance pattern of Mycobacterium tuberculosis in patients at Haji Regional Hospital, East Java Province Method: The type of research is descriptive-retrospective based on primary data from patient medical records and laboratories in the 2019-2022 period Results: The results show that the incidence of drug resistance based on the most OAT in Tuberculosis Drug Resistant Patients at the Haji Hospital of East Java Province in 2019-2022 is a combination of R+H as many as 69 patients (46%) and the origin of the most infection is relapse / recurrence of 73 patients (48.7%) Conclusion: According to the characteristics, the majority of drug-resistant tuberculosis patients at Haji Hospital in East Java Province from 2019-2022 were male patients aged 19-59 years. According to the resistance pattern of M. tuberculosis bacteria, the most common type of drug resistance was MDR-TB (Multi-Drug Resistant Tuberculosis), and the most previous TB history was relapsed patients.